A new species of Ahaetulla Link, 1807 (Serpentes: Colubridae: Ahaetullinae) from India. Issue 9 (12th March 2019) - Deepak, V.; Narayanan, Surya; Sarkar, Vivek; Dutta, Sushil K.; Mohapatra, Pratyush P.
ABSTRACT: A new species of vine snake of the genus Ahaetulla is described from peninsular India. The new taxon is a medium-sized arboreal snake, readily distinguished from all other congeners by morphological and genetic differences. The new species appears to be widely distributed in Eastern Ghats and Central India with the western-most distribution extending into eastern Rajasthan. However, it is relatively rare, with only three specimens being acquired over the past nine years. urn:lsid:zoobank.org:pub:B610BF55-3CEF-4160-9A2C-25A069A82223 urn:lsid:zoobank.org:act:AD84ABAE-F4F5-452C-8EFD-969D191E738B